Prevalence of intestinal parasites among HIV patients at the Yaoundé Central Hospital, Cameroon - Vouking, Marius Zambou (Pan Afr Med J, 2014)
INTRODUCTION: Intestinal parasites are more common in people with HIV, especially in tropical developing countries. This cross-sectional study was carried out to assess the prevalence of intestinal parasites among people with HIV at the Yaoundé Central Hospital Accredited Treatment Centre. METHODS: Structured questionnaires were used to collect clinical information after obtaining consent from the participants. Stool samples were collected from 207 HIV-positive patients for the investigation of intestinal pathogens using direct microscopy, formalin-ether concentration, ZiehlNeelsen modified and Kato-Katz methods. Data was analyzed using Epi-info version 3.4.1. and Microsoft Office Excel 2007. RESULTS: A total of 207 people were recruited. Eighty (38.65%) were male and 127 (61.35%) were female. The overall prevalence of intestinal parasite infections was 57.48% (119/207). The parasites detected in our study population included Entamoeba coli (22.68%), Ascaris lumbricoïdes (22.68%), Entamoeba histolytica(15.93%), Cryptosporidium spp (12.60%), Isospora belli (10.08%), Trichuris trichiura (7.60%), Strongyloïdesstercoralis (5.88%), Ancylostomaduodenale and Necatoramericanus (2.52%). CONCLUSION: At the end of our study, it appears that intestinal parasites still occupy an important place among HIV-positive patients.